Renewing corporate culture through strategy alignment analysis a study case of pt. Dirgantara indonesia - Raharja, Septian Budhi; Welly, John (The Indonesian Journal of Business Administration, 2014)
Abstract. PT. Dirgantara Indonesia (PT.DI) is one of the aircraft manufacturing companies in the world. They facing threats, problems and challenges caused by dynamic environment that pressure this company to change. In order to change and improving its performance also reshaping their company, they initiate restructurization and revitalization program. The program is a large-scale implementation of self-improvement to deal with business challenges also maximizing the opportunities in the present and in the future. Strategy created for successful implementation of the program. In order to substantiate, PT. DI also need to create circumstances in term of culture that will support those strategy. In relation to those changes, the research aims to help harmonize corporate culture and strategy through strategy alignment analysis. This research conducted at PT. Dirgantara Indonesia (PT.DI) located in Bandung particularly on directorate of production as pilot project. Culture can be defining it into a way of group peoples behave. The challenge for organizational leader is to find ways to ensure that the way of people prefer to behave is supportive of what is needed to successfully deliver the company strategy. Using strategy map approach, are first step to examine out strategy and mission and determine what result that company targeted. Then this research expand the strategy map results it into balance scorecard, to define a set of management action that support the attainment of those result. The next step is, define company culture using OCAI and In-depth interview to acquire existing and preferred condition of company culture. After previous analysis an organizational alignment model can be performed and it used to define the operational values that shape the culture of the company. The Final step is implementation plan, divided into three phases, each phases are build to achieve an sustainability condition for the new corporate culture cycles in the company.Â Keywords: Aircraft Manufacturing, Corporate Culture, Organizational Alignment